The Nature and Management of Ethical Corporate Identity: A Commentary on Corporate Identity, Corporate Social Responsibility and Ethics - Balmer, John M. T. (Journal of business ethics, 2007)
In this paper we open up the topic of ethical corporate identity: what we believe to be a new, as well as highly salient, field of inquiry for scholarship in ethics and corporate social responsibility. Taking as our starting point Balmer’s (in Balmer and Greyser, 2002) AC2ID test model of corporate identity – a pragmatic tool of identity management – we explore the specificities of an ethical form of corporate identity. We draw key insights from conceptualizations of corporate social responsibility and stakeholder theory. We argue ethical identity potentially takes us beyond the personification of the corporation. Instead, ethical identity is seen to be formed relationally, between parties, within a community of business and social exchange. Extending the AC2ID test model, we suggest the management of ethical identity requires a more socially, dialogically embedded kind of corporate practice and greater levels of critical reflexivity.